Differential impact of minimal residual disease negativity according to the salvage status in patients with relapsed/refractory B‐cell acute lymphoblastic leukemia. Issue 2 (7th September 2016) - Jabbour, Elias; Short, Nicholas J.; Jorgensen, Jeffrey L.; Yilmaz, Musa; Ravandi, Farhad; Wang, Sa A.; Thomas, Deborah A.; Khoury, Joseph; Champlin, Richard E.; Khouri, Issa; Kebriaei, Partow; O'Brien, Susan M.; et al.
Abstract : BACKGROUND: Minimal residual disease (MRD) assessment predicts survival for patients with newly diagnosed acute lymphoblastic leukemia (ALL). Its significance in relapsed/refractory ALL is less clear. METHODS: This study identified 78 patients with relapsed/refractory B‐cell ALL who achieved a morphologic response with inotuzumab ozogamicin (n = 41), blinatumomab (n = 11), or mini‐hyperfractionated cyclophosphamide, vincristine, and doxorubicin plus inotuzumab (n = 26) during either salvage 1 (S1; n = 46) or salvage 2 (S2; n = 32) and had undergone an MRD assessment by multiparameter flow cytometry at the time of remission. RESULTS: MRD negativity was achieved in 41 patients overall (53%). The MRD negativity rate was 57% in S1 and 47% in S2. Among patients in S1, achieving MRD negativity was associated with longer event‐free survival (EFS; median, 18 vs 7 months; 2‐year EFS rate, 46% vs 17%; P  = .06) and overall survival (OS; median, 27 vs 9 months; 2‐year OS, 52% vs 36%; P  = .15). EFS and OS were similar in S2, regardless of the MRD response. Among MRD‐negative patients who underwent allogeneic stem cell transplantation (SCT), EFS and OS were superior for those who underwent SCT in S1 rather than S2 ( P  = .003 and P  = .04, respectively). Patients in S1 who achieved MRD negativity and subsequently underwent SCT had the best outcomes with a 2‐year OS rate of 65%. CONCLUSIONS: Patients with relapsed/refractory ALL who achieve MRD negativity in S1 can have long‐term survival. Patients in S2 generally have poor outcomes, regardless of their MRD status. Cancer 2017;123:294–302. © 2016 American Cancer Society . Abstract : In adults with relapsed/refractory acute lymphoblastic leukemia who are receiving their first salvage therapy, the achievement of minimal residual disease negativity is an important therapeutic outcome. Patients who achieve minimal residual disease negativity with their first salvage treatment and undergo stem cell transplantation have the best long‐term survival.